Quality of Service Effect and Energy Analysis under AODV in MANET (International Journal of Scientific Research and Management (IJSRM), 2015)
A mobile ad hoc network (MANET) consists of mobile wireless nodes. The communication between mobile nodes is carried out without any central control. Conventional routing protocols may not suffice for real time communications it depends upon the conditions and our requirements. Though there has been significant research in this field. In this paper, we are analyzing the performance of reactive routing protocol (using AODV) and observing its effect on Quality of Service (QoS) of Mobile Ad-hoc Network and we identify the quality of service dependent parameter in mobile ad-hoc network in energy base routing approach, and in that we shows initial energy of each node in joule (unit), in our approach initially all the node configure with initial energy and on the bases of utilization each node energy are discharge Apart from this we also observe quality of service parameter like throughput analysis, packet delivery ratio analysis etc